Sources of Students’ Mental Health Help-Seeking during the Pandemic: a Descriptive Report from Indonesia - Maba, Aprezo Pardodi (Kuras Institute, 2021)
This article investigates the level of help-seeking among Indonesian students during the covid-19 pandemic. Using an online General Help-seeking Questionnaire, the author collected data from several provinces in Indonesia. A total of 411 (Perempuan = 308; Laki-laki = 103; M Usia = 15,61; SD = 1,57) participants were given their consent to be involved in the study. Results showed that 4 (four) primary sources of help will probably be accessed by students when they experience anxiety or fear during covid-19. Those are help from parents, doctors, family members other than parents, and mental health professionals. These findings imply that parents, doctors, family members, and mental health professionals play a significant role in supporting students. Furthermore, these findings also highlight the need for greater awareness and access to mental health services among Indonesian students. Finally, these sources of help should be prepared with first aid mental health skills to provide appropriate support for the students.